'Inheritance Families of Choice'? Lawyers' Reflections on Gay and Lesbian Wills. (June 2016) - Monk, Daniel
Abstract : This article presents the findings of research about the will‐writing practices of gays and lesbians. It develops a conversation between sociological literature about 'families of choice', which is silent about inheritance, and socio‐legal research about 'inheritance families', which is relatively silent about sexuality. It demonstrates how research with lawyers can contribute to thinking about inheritance and complement historical archives about personal life and sexuality. Focusing on funeral rites, partners, ex‐lovers, friendships, children and godchildren, and birth families, the findings reveal how gay men and lesbians have used wills to communicate kinship practices in ways that both converge with and differ from conventional testamentary practices. Examining the findings through the concepts of generationality, family display, connectedness, and ordinariness, and locating them within the recent history of social and legal changes, it complicates and troubles both anti‐normative and individualistic readings of the choices gay and lesbians make in constructing their 'inheritance families'.